2001
DOI: 10.1255/jnirs.291
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Agricultural Soils Using near Infrared Reflectance Spectroscopy and a Fibre-Optic Probe

Abstract: The objective of this work was to investigate the usefulness of near infrared (NIR) reflectance spectroscopy in conjunction with a fibre-optic probe for determining various constituents (total N, organic C, active N, biomass and mineralisable N and pH) in agricultural soils. A NIRSystems model 6500 spectrometer equipped with a fibre-optic reflectance probe was used to scan soil samples (n = 180) obtained from experimental plots at two locations with three replicate plots under plow and no till practices at eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 16 publications
7
30
1
2
Order By: Relevance
“…15%, respectively). For a fairly homogeneous set of ground fine-textured samples (silty loam Ultisols), Reeves and McCarty (2001) also found similar calibration R 2 and CV for Corg and Nt (0.97 and 6%, respectively). For a more heterogeneous set of ground sandy samples originating from different regions of Norway (59°N to 67°N), data from Fystro (2002) showed that validation CV was similar for Corg and Nt but that R 2 was higher for Corg.…”
Section: Comparison Of Prediction Accuracy For Ct and Ntsupporting
confidence: 56%
See 1 more Smart Citation
“…15%, respectively). For a fairly homogeneous set of ground fine-textured samples (silty loam Ultisols), Reeves and McCarty (2001) also found similar calibration R 2 and CV for Corg and Nt (0.97 and 6%, respectively). For a more heterogeneous set of ground sandy samples originating from different regions of Norway (59°N to 67°N), data from Fystro (2002) showed that validation CV was similar for Corg and Nt but that R 2 was higher for Corg.…”
Section: Comparison Of Prediction Accuracy For Ct and Ntsupporting
confidence: 56%
“…However, many authors tested several preprocessing methods and selected the most suitable for each property (Reeves and McCarty, 2001;McCarty et al, 2002;Russell, 2003;Sørensen and Dalsgaard, 2005). Moreover, some other authors have reported that normalisation did not improve the calibration (Shepherd and Walsh, 2002).…”
Section: Effect Of the Spectrum Preprocessingmentioning
confidence: 99%
“…It has proven to be a rapid and efficient technique for estimating a variety of soil properties, including the SOM content [3,13,14]. The prediction accuracies of the VNIR models for SOM content have, however, varied from less than satisfactory [15] to satisfactory [16], depending on the land use [7], the source of the VNIR data, the calibration methods, scanning environments, soil chromophores (e.g., iron oxide) and even the spectroscopic instruments [10,11,13,17]. The mechanisms for the VNIR estimation of SOM content are its broad absorptions in the visible region, due to chromophores and the darkness of humic acid, and the absorptions in the NIR region from the overtones of O-H, C-H and N-H, or their combination [13,18].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has suggested that visible and nearinfrared (VIS/NIR, 0.4-2.5 μm) diffuse reflectance spectroscopy (DRS) can provide a relatively inexpensive means of characterising the physical, chemical and biological properties of soils (Ben-Dor and Banin 1994; Reeves III et al 1999;Reeves III and McCarty 2001;Shepherd and Walsh 2002;Islam et al 2003;Dunn et al 2002). DRS is an indirect analytical method that is based on the development of empirical models in which the concentration of a constituent is predicted from multivariate spectral data (Awiti et al 2008).…”
Section: Introductionmentioning
confidence: 99%